The Analysis of Womenâ€™s Representation in the House of Representatives of Central - Rapha, Albert J.; Subowo, Ari; Afrizal, Teuku (Journal of Public Policy and Management Review, 2021)
The existence of women frequently perceived as â€œsecond sexâ€ in society. In fact, their voices, ideas, and gender roles are often ignored. Thus, in order to support womenâ€™s right the United Nations through CEDAW encourages the achievement of 30% quota of womenâ€™s representation in legislative institution as the entrance of womenâ€™s interests in the policy-making process. Furthermore, the UN recommendation has been ratified by Indonesian government to produce the guidelines to spur womenâ€™s political participation through Ministerial Women Empowerment and Child Protection Regulation 07/2013 on Increasing Womenâ€™s Political Participation in Legislative. Nevertheless, the emergence of this affirmative policy has not been able to attain the target of least 30% representation in the legislative institution, including the House of Representatives of Central Java 2019-2024. Further, this research emphasizes about the factual condition of womenâ€™s political representation and why the womenâ€™s political representation enhancement policy still yet spur the womenâ€™s representation rate in the House of Representatives of Central Java 2019-2024. By using descriptive-qualitative method and System Theory basis, the author tries to scrutinize more deeply about the reality in the field based on four main factors: policy cognition, socio-culture, human resources, and political factor. According to the result, this research finds various hurdles on the policy implementation, including the deep rooted of patriarchy culture, the lack of womenâ€™s capability as policy makers, and various political factors.